Stress Granules in the Post-transcriptional Regulation of Immune Cells - Curdy, Nicolas; Lanvin, Olivia; Cadot, Sarah; Laurent, Camille; Fournié, Jean-Jacques; Franchini, Don-Marc (Frontiers in Cell and Developmental Biology, 2021)
Immune cell activation triggers transcriptional and translational programs eliciting cellular processes, such as differentiation or proliferation, essential for an efficient immune response. These dynamic processes require an intricate orchestration of regulatory mechanisms to control the precise spatiotemporal expression of proteins. Post-transcriptional regulation ensures the control of mRNA metabolism and appropriate translation. Among these post-transcriptional regulatory mechanisms, stress granules participate in the control of protein synthesis. Stress granules are ribonucleoprotein complexes that form upon stress, typically under control of the integrated stress response. Such structures assemble upon stimulation of immune cells where they control selective translational programs ensuring the establishment of accurate effector functions. In this review, we summarize the current knowledge about post-transcriptional regulation in immune cells and highlight the role of stress sensors and stress granules in such regulation.